PERANCANGAN SISTEM INFORMASI BIMBINGAN KONSELING (BK) SEKOLAH - Syamsul Alam (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
Counseling Information System in question is data management student at the LB which includes data of student, track record, note problems, home visits, the results of sociometry, attendance, assessment and counseling outcomes. Results showed that making student information system data processing carried out by the authors to help teachers BK in the data processing required.